"The Faithful Work of Drowning.": A Reparative Reading of Ocean Vuong's "Telemachus". Issue 2 (2nd April 2020) - Chavez, Jeremy De; Lin, Cassie Jun
Abstract: In this short essay, we speculate on what it might mean to de-privilege a paranoid orientation in favor of a reparative one that strategically withholds suspicion "to open unexpected possibilities, ways of thinking, gestures and tones, " to use the words of Heather Love. Toward that goal, we offer a reparative reading of Ocean Vuong's "Telemachus", part of his award-winning collection Night Sky with Exit Wounds, and suggest that it is a poem that writes back to the Western canon. However, we resist evaluating the poem as either subversive or reactionary to argue instead that the poem invites readings that pay close attention to affects oriented toward reparation, which establishes a relation to canonical texts that resists being defined by categories such as good/bad and center/margin, binaries that often undergird paranoid critique.